1997
DOI: 10.1046/j.1469-8137.1997.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminium on ion uptake and H+ release by maize

Abstract: SUMMARYThe aim of this study was to quantify the long-term effects of Al in solution on mineral ion uptake and associated H^ release by the roots of maize cultivated in conditions compatible with field data. Two maize {Zea mays L.) cvs of differing sensitivity to Al were compared. The culture w^as conducted in hydroponic conditions for culture periods of 2-5 d in the presence of 0-30 /xm Al. Proton fluxes were localized along the roots using a videodensitometry method with bromocresol green on agarose gel.Alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Both sensitive and tolerant genotypes of wheat had presented a decrease in K and Mg contents in roots, whereas Ca, Al, Si contents increased [89]. It was reported that NO 3− uptake by soybean was decreased when Al concentration in solution increased from 10 to 50 µM [90] whereas, Al reduced Cl − and NO 3− uptake in maize [91]. It is also observed that Al toxicity is closely related to nitrogen metabolism [92].…”
Section: Nutritional Imbalancementioning
confidence: 67%
“…Both sensitive and tolerant genotypes of wheat had presented a decrease in K and Mg contents in roots, whereas Ca, Al, Si contents increased [89]. It was reported that NO 3− uptake by soybean was decreased when Al concentration in solution increased from 10 to 50 µM [90] whereas, Al reduced Cl − and NO 3− uptake in maize [91]. It is also observed that Al toxicity is closely related to nitrogen metabolism [92].…”
Section: Nutritional Imbalancementioning
confidence: 67%
“…Exchangeable aluminum decreases nutrient availability to plants by lowering phosphorus, magnesium, and calcium absorption (Malavolta et al 1977;Marschner 1989), as well as inducing a drastic reduction in anion uptake by plant roots (Calba & Jaillard 1997). However, there is evidence of high species richness in sites where plant growth is limited by several nutrients (Braakhekke 1980;Tilman 1982; Harpole & Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Rufyikiri (2000), these changes in pH indicate that those of the input solutions are of a little importance for interpreting rhizospheric phenomena, such as nutrient uptake and element toxicity, that could be influenced by the proton activity. In this experiment, nutrient solutions were not adjusted and maintained at the same pH by the addition of acid or basic solution as in other studies (Calba & Jaillard, 1997 ;Ishikawa & Wagatsuma, 1998). However, the acidification induced by roots, especially of Al !…”
Section: mentioning
confidence: 99%